Targeting agricultural research for development in the Semi-Arid Tropics of Sub-Saharan Africa - Freeman, H.; Rohrbach, D.; Ackello-Ogutu, Ch. (Nairobi (Kenya), 2002)
Sumarios (En, Fr)
Ilus.; 35 ref.
Keywords: INVESTIGACION; DESARROLLO AGRICOLA; ZONA TROPICAL; COMUNIDADES RURALES; TECNOLOGIA; AFRICA